Faktor Penentu Kepatuhan Pajak UMKM Kuliner di Lampung Selatan: Tarif, Pengetahuan, dan Sanksi - Chairian Tomy; Fachrur Rozi (Journal of Economics and Business, 2025)
This study was conducted to explain the effect of changes in tax rates, tax knowledge, and tax sanctions on tax compliance of MSMEs. The population in this study were MSMEs in the culinary sector in Sleman Regency. The sampling technique was Simple Random Sampling with the calculation of the number of samples using the Slovin method. The total sample in this study was 99 MSMEs. The results of this study indicate that tax knowledge and tax sanctions have an effect on MSME tax compliance. While tax rates do not affect MSME tax compliance.